2019
DOI: 10.1177/2331216519887815
|View full text |Cite
|
Sign up to set email alerts
|

Pupillometry as an Objective Measure of Sustained Attention in Young and Older Listeners

Abstract: The ability to sustain attention on a task-relevant sound source while avoiding distraction from concurrent sounds is fundamental to listening in crowded environments. We aimed to (a) devise an experimental paradigm with which this aspect of listening can be isolated and (b) evaluate the applicability of pupillometry as an objective measure of sustained attention in young and older populations. We designed a paradigm that continuously measured behavioral responses and pupillometry during 25-s trials. Stimuli c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 91 publications
8
58
0
Order By: Relevance
“…Our results suggest that developing more sensitive auditory sustained attention tasks (e.g. Zhao et al, 2019 ) may be crucial for accurate assessment of older listeners' scene analysis ability.…”
Section: A Link Between Change Detection and Auditory Sustained Attenmentioning
confidence: 81%
“…Our results suggest that developing more sensitive auditory sustained attention tasks (e.g. Zhao et al, 2019 ) may be crucial for accurate assessment of older listeners' scene analysis ability.…”
Section: A Link Between Change Detection and Auditory Sustained Attenmentioning
confidence: 81%
“…Using longer stimuli (30 seconds) in this study, however, resulted in smaller dilation relative to the baseline, in both low and high SNR conditions (Fig 2C). This is probably caused by the sensitivity of the pupil to task alertness, which could be more pronounced in the first seconds of the trial and has previously been observed in longer pupil data collection as well (e.g., [37], [51]). The relative decrease of MPD measurement over 30 seconds might be due to evoked pupil dilation to the background noise in the baseline.…”
Section: Pupillometrymentioning
confidence: 77%
“…Metrics used to characterize the TEPR are the mean dilation, the maximal value, and the latency of the peak response to a particular stimulation, the allocation of more resources (higher load) leading to larger pupil dilation. It is, however, a complex experimental model with several crucial variables, as previous works have shown that TEPR characteristics are modulated by the complexity of the cognitive task, by attentional or memory load, and by motivation ( Kahneman and Beatty, 1966 ; Kahneman, 1973 ; Ben-Nun, 1986 ; Peelle, 2018 ; Zhao et al, 2019 ; and see Beatty, 1982 ; Beatty and Lucero-Wagoner, 2000 ; Winn et al, 2018 ; Zekveld et al, 2018 for reviews).…”
Section: Introductionmentioning
confidence: 99%